Development of isotope-enriched phosphatidylinositol-4-and 5-phosphate cellular mass spectrometry probes - Joffrin, AM; Saunders, AM; Barneda, D; Flemington, V; Thompson, AL; Sanganee, HJ; Conway, SJ (Royal Society of Chemistry, 2020)
Synthetic phosphatidylinositol phosphate (PtdInsPn) derivatives play a pivotal role in broadening our understanding of PtdInsPn metabolism. However, the development of such tools is reliant on efficient enantioselective and regioselective synthetic strategies. Here we report the development of a divergent synthetic route applicable to the synthesis of deuterated PtdIns4P and PtdIns5P derivatives. The synthetic strategy developed involves a key enzymatic desymmetrisation step using Lipozyme TL-IM®. In addition, we optimised the large-scale synthesis of deuterated myo-inositol, allowing for the preparation of a series of saturated and unsaturated deuterated PtdIns4P and PtdIns5P derivatives. Experiments in MCF7 cells demonstrated that these deuterated probes enable quantification of the corresponding endogenous phospholipids in a cellular setting. Overall, these deuterated probes will be powerful tools to help improve our understanding of the role played by PtdInsPn in physiology and disease.